MAST CELLS ARE KEY PARTICIPANTS IN THE PATHOGENESIS OF IMMUNOINFLAMMATORY DISEASES - E. O. Baglay; A. I. Dubikov (Научно-практическая ревматология)
Mast cells are an integral component of the pathogenetic  chain of immune inflammation in the body's tissues in different diseases. The mechanisms  underlying the proinflammatory effects of mast cells remain inadequately investigated. Their study may contribute to the optimization of therapy for different diseases, including chronic arthritis.